PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI PT PEGADAIAN (PERSERO) CABANG PEMBANTU SIMPANG LIMUN MEDAN - Br Sagala, Melvi Yuliana; Sianturi, Charles M.; Sinaga, Kepler (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The purpose of this study was to measure the effect of service quality on customer satisfaction at PT Pegadaian (Persero) Simpang Limun Medan Branch Office. This study used a quantitative method with a nonprobability sampling technique and an accidental sampling approach with a sample size of 30 respondents. Data collection techniques were carried out with primary and secondary data, using multiple regression analysis, which began with validity, reliability, classical assumptions, determination coefficient, F test, and t test with the help of SPSS Statistics version 22. Based on the partial t test and simultaneous F test, the results of the study showed that the variables of physical evidence, reliability, responsiveness, and assurance had a positive and significant effect on customer satisfaction, while the empathy variable had no significant effect. Based on the coefficient of determination (R²), it is known that the five independent variables explain 72.5% of the variability in customer satisfaction, while the remaining 27.5% is explained by other variables not examined in this study.